English in the real world: What classroom pedagogy has not taught. Issue 2 (1st October 2019) - Bao, Dat
AbstractThis article narrates the experiences of eight Japanese individuals who travelled to Melbourne, Australia, not to study English in a formal classroom, but to activate their language skills in a genuine social context. Speakers were willing to take risk in the social process to acquire fluency and develop confidence. Based on data generated from two years' observation of and interviews with the participants, the author documented the pleasure and the challenges that occur in their unique experience. The project reveals a range of preferences, strategies and tension in the languageusing environment. Educational implications are drawn from several key characteristics of this self-motivated experiential model that may be absent in the current academic discourse in English-language teaching practice.